The evaluation of organizational well-being in the public sector: an integration of the ANAC questionnaire - Emanuel, Federica; Bertola, Lara; Colombo, Lara (La Medicina del Lavoro, 2018)
Background: In Italy, the work-related stress and organizational well-being evaluation is subject to specific norms and regulations. The Italian National Anti-Corruption Authority (Autorità Nazionale Anticorruzione - ANAC) has developed a questionnaire to assess the organizational well-being of the employees in Public Administration Institutions. Objectives: The study aims to analyse, according to the Job Demands-Resources Theory, the relationship between some job demands (workload, discrimination) and job resources (supervisors and colleagues support, job autonomy, fairness, career opportunities, membership), and some outcomes (work-related stress, emotional exhaustion, job satisfaction). Methods: The research involved a public administration and was conducted through a self-report questionnaire (N=414, 60% of the employees). The ANAC questionnaire was integrated with measures from national and international literature on the topic of well-being and stress at work. Results: Multiple regression analyses highlighted the relationship between outcomes, job demands and resources. Work-related stress showed a positive relation with demands (work load β  coefficient=0.22; perceived discrimination β=0.14) and a negative one with some resources (supervisors’ support β=-0.21 and membership β=-0.11). Emotional exhaustion had a negative relationship with some job resources, specifically career opportunities (β=-0.14), autonomy (β=-0.21) and membership (β=-0.25). Job satisfaction showed a positive relationship with all job resources considered. Conclusions: The study seeks to integrate the assessment of well-being and work-related stress thus highlighting the importance of linking the different outcomes with job demands and resources. The results identify possible practices to promote well-being in the organization.